The development of mimusops elengi as cosmetic ingredient - Mumtaz M.Sultan Suhai Buddeen (2013)
This study was focused on the development of Mimusops elengi (tanjung) fruit as cosmetic ingredients by determining its antioxidant activity using 2, 2-Diphenyl-1- picrylhydrazyl (DPPH) radical scavenging assay and the presence of phenolic compound using Thin Layer Chromatography (TLC) plates by 5% ferric chloride detection reagent. Fruits of Mimusops elengi were extracted with methanol, ethanol and ethyl acetate. Kernel of the fruit was extracted with petroleum ether. Results indicated concentration at fifty percent inhibition (IC₅₀) for DPPH free radical scavenging activity of ethyl acetate solid part (EASP), ethanol solid part (ESP), ethyl acetate liquid part (EALP), ethanol liquid part (ELP), methanol solid part (MSP) and methanol liquid part (MLP) extract were 40.08 ± 6.96,43.94 ± 4.44, 65.17 ± 4.16, 67.54 ± 16.23, 77.03 ± 8.78 and 92.18 ± 9.94 μg/ml respectively. Petroleum ether (PE) kernel extract did not manage to attain IC₅₀ within the range of concentration tested. On the other hand, lipid content of kernel extract was determined by soxhlet apparatus and lipid content yield was 24.18% per gram. Results from TLC sprayed with 5% ferric chloride detection reagent revealed the presence of phenolic substance in all extracts except PE kernel extract. The chemical profiles of extracts were determined by TLC which sprayed with 5% sulphuric acid in 70% ethanol and iodine water as detection reagents. From this present study, it can be concluded that antioxidant activity of all extracts have the potential to be an alternate source of natural antioxidants after further evaluate.